Relationship of Ergonomic Risks with Muscoloskeletal Disorders (Msds) in Rubber Production Part Workers at Pt. X Jambi in 2024 - Aisyah, Fuadhatul; Rini, Willia Novita Eka; Halim, Rd. (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine the relationship between ergonomic risks and complaints of musculoskeletal disorders (MSDs) in rubber production workers at PT X Jambi in 2024. This study is a quantitative study using an observational design with a cross sectional approach. The population in this study were 52 people with a research sample of 47 people using total sampling as a sampling method. Based on the results of the study, the prevalence of high musculoskeletal disorder (MSDs) complaints was felt by 36 (76.6%) rubber production workers. The results of bivariate analysis showed that the variable duration of work with an unfavorable category was 21 (87.5%) with a value of (p = 0.144 > 0.05), the weight of the load with a risk category was 31 (91.2%) with a value of (p = 0.000 < 0.05), work attitude with a risk category was 31 (91.2%) with a value of (p = 0.000 < 0.05). 05), work attitude with non-ergonomic category as many as 27 (87.1%) with value (p=0.029 < 0.05), ergonomic risk level with high category as many as 28 (82.4%) with value (p=0.246 > 0.05), and work frequency with abnormal category as many as 27 (87.1%) with value (p=0.029 < 0.05).